Leadership in Action: Finding Yourself: How Social Identity Affects Leadership - Ruderman, Marian; Ernst, Christopher (Center for Creative Leadership, 2010)
In today's increasingly volatile and complex organizational environment, it's as important as ever for leaders to understand themselves. But it's no longer enough for them to be aware of their capabilities, motivations, styles, and values. Leaders now must also gain knowledge of their social identities-their membership in certain social groups defined by categories such as gender, race, and religion and the implications of belonging to these groups.
Keywords: Leadership